Preterm birth in low-middle income Countries - Alim, Swarray-Deen (2024)
Preterm birth (PTB), remains a major cause of significant morbidity and mortality world-wide with about 12–15million preterm births occurring every year. Although the overall trend is decreasing, this is mainly in high-income countries (HIC). The rate remains high in low-and middle-income countries (LMIC) varying on average between 10 and 12% compared to 9% in HIC. The pathogenesis of PTB is complex and multifactorial. Attempts to reduce rates that have focused on PTB as a single condition have in general been unsuccessful. However, more recent attempts to phenotype PTB have resulted in targeted preventative approaches which are yielding better results. Prevention (primary or secondary) is the only approach that has been shown to make a difference to rates of PTB. These include identifying risk factors pre-pregnancy and during pregnancy and instituting appropriate measures to address these. In LMIC, although some approaches that have been shown to be effective in some HIC are adaptable, there is a need to involve stakeholders at all levels in utilizing evidence preferrably generated in LMIC to implement strategies that are likely to reduce the rate of PTB. In this review, we focus on prevention and how to involve policy makers in the process of applying evidence into policy that would reduce PTB in LMIC.